The Evaluation of Medical Services presented to Students of physical education and Sport Sciences College/ university of Baghdad - Mahdi, Abdalhadi Hameed; Hussein, Ali Kamal; Znad, Bashar Mohammed (Journal of Physical Education, 2021)
The research aimed at identifying the medical services present to the students of physical education and sport sciences/university of Baghdad.  The researchers hypothesized significant statistical differences in medical services evaluation. They used the descriptive method on (274) forth year College of physical education and sport sciences college students, university of Baghdad for the academic year 2021 – 2022. Only (150) students’ questionnaire was used in this researcher. The questionnaire included eight axis; each axe consisted of five questions (safety and first aids, medical examination and periodical comprehensive medical test, injury treatment, healthy environment, contagious diseases control, sports nutrition, personal health, psychological care). The research came up with many conclusions and recommendations.